Characteristics and Prevalence of Vancomycin-variable Enterococcus faecium bacteremia in southern Taiwan - Chi-Jung Lu; Wei-Chun Hung; Zi-Han Lan; Po-Liang Lu; Chun-Yu Lin; Yen-Hsu Chen; Tun-Chieh Chen; Chung-Hao Huang; Ya-Ting Chang; Chun-Yuan Lee; Yu-Te Tsai; Shang-Yi Lin (Journal of Microbiology, Immunology and Infection, 2024)
Background: Vancomycin-variable enterococci (VVE) are vanA-carrying Enterococcus faecium that are phenotypically susceptible to vancomycin and can only be detected using molecular methods, leading to the possibility of treatment failure and posing threats to infection control. This study aimed to determine the prevalence of VVE and its associated clinical risk factors. Methods: This retrospective study was conducted in two hospitals in southern Taiwan. Patients with phenotypically vancomycin-susceptible E. faecium bacteremia were enrolled between 2017 and 2021. VVEs were defined as isolates harboring the vanA gene that were phenotypically susceptible to vancomycin. Vancomycin-susceptible E. faecium (VSE) isolates were phenotypically susceptible to vancomycin and lacked vanA or vanB genes. Results: Of the 142 enrolled patients, 121 (85.2%) had VSE and 21 (14.8%) had VVE. Resistance rates to penicillin, tetracycline, and fosfomycin were higher in VVE isolates. Malignancy (adjusted odds ratio [aOR] = 4.87; 95% confidence interval [CI] 1.54–15.41, p = 0.007) and central venous catheter usage (aOR = 4.69; 95% CI 1.49–14.78, p = 0.008) were the independent risk factors associated with VVE bacteremia. Being male (aOR = 0.12, CI 0.03–0.44, p = 0.002) was less likely to be associated with VVE bacteremia. Although VVE was not associated with 30-day mortality (38.1% [VVE] vs. 35.5% [VSE], p = 0.822), one case of subsequent vancomycin-resistant enterococci infection in the VVE group with vancomycin treatment (4.8%, 1/21) was identified, which led to subsequent mortality. Conclusions: The prevalence of VVE was high among E. faecium isolates with vancomycin-susceptible phenotypes in southern Taiwan. Although the current study revealed that VVE bacteremia was not associated with poor clinical outcome, further multicenter surveillance survey is recommended to evaluate the possible impact of VVE on public health in Taiwan.